Stakeholder perceptions on broiler chicken welfare during first-day processing and the pre-slaughter phase: a case study in Belgium. Issue 3 (2nd July 2020) - Lambrecht, Evelien; Jacobs, Leonie; Delezie, Evelyne; De Steur, Hans; Gellynck, Xavier; Tuyttens, Frank
SUMMARY: Day of hatch and pre-slaughter processing are stressful events (involving selection, handling and transport) for broiler chickens, putting pressure on welfare, which has economic consequences. This case-study documented common industry practices and evaluated poultry industry stakeholder perceptions related to broiler welfare during day-of-hatch processing and the pre-slaughter phase. Twenty-three individual in-depth interviews were conducted with representatives of key stakeholders in the Flemish poultry sector: hatchery personnel (five), farmers (six), poultry catchers (two), transporters (three) and slaughterhouse personnel (seven). The findings showed various factors influencing broiler welfare during day of hatch processing and the pre-slaughter phase, with some discrepancies between stakeholder views and the scientific evidence. While stakeholders perceived the day of hatch processing procedures of chicks to be relatively under control, with no major issues, literature points out several issues, including first-week mortality and time without feed and water as major welfare problems. For broilers at slaughter age, the industry stakeholders' views aligned well with scientific evidence on major welfare issues, such as injuries, thermal stress, mortality during fasting, catching, loading, transportation and lairage. This study provides novel insights in stakeholder perceptions, and potential avenues for future research and actions to reduce animal welfare problems in the poultry sector.